2020
DOI: 10.3389/fgene.2020.00245
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Autophagy-Associated Biomarkers and Corresponding Regulatory Factors in the Progression of Colorectal Cancer

Abstract: Autophagy is a self-degradation process that maintains homeostasis against stress in cells. Autophagy dysfunction plays a central role in the development of tumors, such as colorectal cancer (CRC). In this study, autophagy-related differentially expressed genes, their downstream functions, and upstream regulatory factors including RNAbinding proteins (RBP) involved in programmed cell death in the CRC were investigated. Transcription factors (TFs) and miRNAs have been shown to mainly regulate autophagy genes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Overexpression of DDX17 enhances malignant migration and invasion of glioma cells by repressing beclin1 expression [ 29 ]. Zhang et al reported that DDX17 is important for the autophagy regulatory network through clinical data analyses of diverse stages for colorectal cancer [ 30 ]. Based on these reports, we investigated whether DDX17 regulates autophagy process in lung adenocarcinoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of DDX17 enhances malignant migration and invasion of glioma cells by repressing beclin1 expression [ 29 ]. Zhang et al reported that DDX17 is important for the autophagy regulatory network through clinical data analyses of diverse stages for colorectal cancer [ 30 ]. Based on these reports, we investigated whether DDX17 regulates autophagy process in lung adenocarcinoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Promising results already exist in this regard where a defect in autophagy induction correlated with poor TB disease outcomes [ 72 ]. Supporting this notion, autophagy proteins (LC3B and p62) are currently being investigated as prognostic markers in cancer [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. After phagosomal damage, it is still unknown which M. tb proteins and phagosomal membrane proteins become ubiquitinated leading to autophagy activation.…”
Section: Discussionmentioning
confidence: 99%
“…Some RNA-binding proteins, such as DDX17, SETDB1, and POLR3, regulate autophagy in CRC by developing tumors and then searching for potential therapeutic targets in CRC. 11 Abnormal expression of NTF4 in CRC also affects autophagy. Knock-out of NTF4 prevents the transition of epithelial cells into mesenchyme in CRC and activates autophagy through the interaction of autophagy-related gene 5 (ATG5) with the mitogen-activated protein kinase pathway, thereby inhibiting the proliferation, migration, and invasion of the cells, along with clone-forming capacity, while promoting the arrest of cell cycle.…”
Section: Discussionmentioning
confidence: 99%